The effect of health literacy and health empowerment on quality of life in the elderly - Ciftci, Necmettin; Yildiz, Metin; Yildirim, Omer (Wiley, 2023)
BackgroundThis study was conducted to determine the effect of health literacy and health promotion on quality of life in the elderly. MethodThis descriptive and cross-sectional study was conducted with 981 elderly individuals aged 65 years and older in Turkey. 'Introductory Information Form', 'Health Literacy Scale', 'Elderly Health Empowerment Scale' and 'Quality of Life Scale for the Elderly' were used to collect data. The research data were analyzed by Structural Equation Modelling using SPSS 22.0, AMOS V 24.0, G*Power 3.1 statistical package programs. ResultsHealth literacy level increased health empowerment level (t = 5.929 R-2 = 0.035, P < 0.05). Health literacy level increased quality of life level (t = 13.439 R-2 = 0.156, P < 0.05). Health empowerment level was found to affect quality of life level (t = 17.746 R-2 = 0.243, P < 0.05). Health empowerment was found to have a mediating role in the effect of health literacy on quality of life (beta = 0.502, 95% confidence interval (lower bound-upper bound) = 0.013-1.038). It was determined that the model created in line with the hypotheses was compatible and the model fit indices x(2)/SD = 4.919, root mean square error of approximation = 0.06, comparative fit index = 0.91, fit index = 0.95, adjusted fit index = 0.93, incremental fit index = 0.91 were within the desired limits. ConclusionsAs the level of health literacy increases, so does the level of health empowerment and quality of life. As the level of health empowerment increases, so does the level of quality of life. It is recommended to design policies that will help to increase the health literacy and health empowerment levels of the elderly. Longitudinal studies on quality of life in the elderly are recommended.
Keywords: Elderly; Health Empowerment; Health Literacy; Quality Of Life; Epidemiology; Scale; Model